STEM-BASED E-MODULE IN IMPROVING STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY: A NEEDS ANALYSIS FOR INDONESIAN STUDENTS - Komarudin, Komarudin (Program Studi Pendidikan Matematika FIP UNHASY, 2022)
Creative thinking is one of the 21st century thinking skills, because it allows individuals to adapt quickly to various changes that occur. The integration of e-modules and STEM is expected to improve students' mathematical creative thinking skills. This study aims to analyze the need for teaching materials in the form of STEM-based e-modules in improving students' mathematical creative thinking skills. The subjects of this study were 14 mathematics teachers and 39 students from various school levels in Indonesia. Data collection is done through a questionnaire technique. The research instrument consisted of a questionnaire on the needs of teachers and students for STEM-based e-modules, each with 14 questions and 13 questions. The results showed that teachers and students felt that it was necessary to develop an integrated STEM e-module in improving students' own mathematical creative thinking skills.